Composition and threaded joint for pipes having a lubricating coating layer made of said composition

The application of a lubricating coating layer containing polyisobutylene and other components to tube threaded joints addresses the challenges of seizure resistance and high torque performance, ensuring reliable operation and airtightness during repeated cycles.

JP7657055B2Active Publication Date: 2025-04-04NIPPON STEEL CORPORATION +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020565706
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-07
Filing Date
2019-12-25
Publication Date
2025-04-04
Estimated Expiration
2039-12-25

AI Technical Summary

Technical Problem

Existing tube threaded joints in oil well pipes face challenges with seizure resistance and high torque performance, particularly during repeated tightening and loosening operations, which can lead to irreparable seizure and reduced airtightness.

Method used

A lubricating coating layer composed of polyisobutylene, metal soap, wax, and a metal salt of basic aromatic organic acids is applied to the contact surfaces of the tube threaded joint, enhancing both seizure resistance and high torque performance.

Benefits of technology

The lubricating coating layer significantly improves the seizure resistance and high torque performance of the tube threaded joints, allowing for repeated fastening without seizure and maintaining airtightness even after repeated cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657055000004
    Figure 0007657055000004
  • Figure 0007657055000005
    Figure 0007657055000005
  • Figure 0007657055000006
    Figure 0007657055000006
Patent Text Reader

Abstract

The present disclosure provides a composition for obtaining a tubular threaded joint having excellent galling resistance and excellent high-torque performance, and a tubular threaded joint having a lubricating coating layer formed from the composition and having excellent galling resistance and excellent high-torque performance. The composition of the present disclosure is for forming a lubricating coating layer (21) on a tubular threaded joint and contains polyisobutylene, a metal soap, a wax, and a metal salt of a basic aromatic organic acid. The tubular threaded joint of the present disclosure comprises a pin (3) having a pin-side contact surface (34) including a pin-side thread portion, a box (4) having a box-side contact surface (44) including a box-side thread portion, and a lubricating coating layer (21) made of the above composition as an outermost layer on at least one of the pin-side contact surface (34) and the box-side contact surface (44).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composition and a threaded tubular joint provided with a lubricating coating layer comprising the composition. [Background technology]

[0002] Oil well tubular goods are used for the extraction of oil and natural gas fields. Oil well tubular goods are made by connecting multiple steel pipes according to the depth of the well. Steel pipes are connected by screwing together pipe thread joints formed at the ends of the steel pipes.

[0003] A typical tubular threaded joint used for fastening oil country tubular goods includes a pin-box structure consisting of a member called a pin and a member called a box. The pin includes a pin-side threaded portion formed on the outer circumferential surface of the end of the steel pipe. The pin may further include a pin-side metal seal portion and a pin-side shoulder portion. The box includes a box-side threaded portion formed on the inner circumferential surface of the end of the steel pipe. The box may further include a box-side metal seal portion and a box-side shoulder portion. When the steel pipes are screwed together, the pin-side threaded portion and the box-side threaded portion come into contact with each other. When the tubular threaded joint includes a metal seal portion and a shoulder portion, the metal seal portions and the shoulder portions come into contact with each other during screwing.

[0004] During the operation of lowering oil well tubular goods, due to various reasons such as trouble, the oil well tubular goods may be pulled up from the oil well, and then the threaded pipe joint that was once tightened may be loosened and then tightened again before being lowered. The threaded parts of the pin and box, the metal seal part and the shoulder part are repeatedly subjected to strong friction when the steel pipe is tightened and unscrewed. If these parts do not have sufficient durability against friction, galling (irreparable seizure) will occur when the pipe is repeatedly tightened and unscrewed. Therefore, pipe threaded joints are required to have sufficient durability against friction, i.e., excellent seizure resistance.

[0005] Conventionally, in order to improve the seizure resistance and airtightness of tubular threaded joints, a viscous liquid lubricant (grease lubricant) containing heavy metal powder, called "dope" or "compound grease", has been used. Compound grease is applied to the contact surfaces of the threaded joint (i.e., the threads, or, if the tubular threaded joint has a metal seal and shoulder, the threads, metal seal and shoulder). Examples of compound grease are described in API standard BUL 5A2.

[0006] However, heavy metals such as Pb contained in compound grease may have an impact on the environment. For this reason, various lubricating coatings have been proposed as new lubricants to replace compound grease.

[0007] WO 2009 / 057754 (Patent Document 1) and WO 2014 / 024755 (Patent Document 2) propose compositions for forming a lubricating coating layer that is excellent in seizure resistance and does not contain heavy metals that may have an impact on the environment.

[0008] The composition for forming a lubricating coating on a tubular threaded joint described in Patent Document 1 contains one or both of rosin and calcium fluoride, metal soap, wax, and a metal salt of a basic aromatic organic acid. This composition for forming a lubricating coating does not substantially contain harmful heavy metals such as lead, so it has a very small impact on the global environment. In addition, the lubricating coating formed from this composition has excellent rust prevention properties and suppresses the occurrence of rust during storage of the tubular threaded joint. Therefore, Patent Document 1 describes that the tubular threaded joint can maintain its lubricating function even if it is repeatedly tightened and loosened, and can ensure airtightness after tightening.

[0009] The composition for forming a lubricating coating on a tubular threaded joint described in Patent Document 2 contains melamine cyanurate, a basic aromatic organic acid metal salt, and one or more selected from rosin-based substances, wax, metal soap, and lubricating powders. Patent Document 2 describes that if a lubricating coating is formed using this composition, the generation of rust on the tubular threaded joint is suppressed, the lubricating function is sustained even after repeated tightening and loosening, and airtightness can be ensured after tightening. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2009 / 057754 [Patent Document 2] International Publication No. 2014 / 024755 Summary of the Invention [Problem to be solved by the invention]

[0011] When tightening a tubular threaded joint, the torque at the end of tightening (hereinafter referred to as tightening torque) is set so that sufficient sealing surface pressure is obtained regardless of the amount of thread interference. In the final stage of tightening, the surface pressure between the threads increases. Even when the surface pressure increases, if the torque can be increased steadily without seizing, it becomes easy to adjust the tightening torque. Therefore, tubular threaded joints are required to have the performance to steadily increase the torque even under high surface pressure. Hereinafter, this performance will be referred to as high torque performance.

[0012] In the case of a tubular threaded joint with a shoulder, high torque performance is defined as the ability to maintain the torque increase rate immediately after shouldering in the region where the rotation speed is higher than the shouldering torque in a torque chart showing the relationship between the rotation speed and torque of a steel pipe when tightened. In the case of a tubular threaded joint with a shoulder, it can be expressed as torque-on-shoulder resistance ΔT'.

[0013] When a tubular threaded joint has a shoulder portion, the shoulder portions of the pin and the box come into contact with each other during tightening. The torque that occurs at this time is called shouldering torque. When tightening a tubular threaded joint, after the shouldering torque is reached, further tightening is performed until make-up is complete. This increases the airtightness of the tubular threaded joint. If the threads are tightened excessively, the metal that constitutes at least one of the pin and the box begins to undergo plastic deformation. The torque that occurs at this time is called yield torque. Torque-on-shoulder resistance ΔT' refers to the difference between the shouldering torque and the yield torque.

[0014] When a tubular threaded joint has a shoulder, if the torque-on-shoulder resistance ΔT' is large, the make-up torque can be easily adjusted. Even when a tubular threaded joint does not have a shoulder, if the torque increases steadily under high surface pressure, the make-up torque can be easily adjusted.

[0015] The compositions disclosed in Patent Documents 1 and 2 can also form lubricating coatings that improve seizure resistance and facilitate adjustment of make-up torque. However, it is preferable that other compositions and lubricating coatings also provide excellent seizure resistance and high torque performance.

[0016] An object of the present disclosure is to provide a composition for obtaining a tubular threaded joint having excellent seizure resistance and excellent high torque performance, and a tubular threaded joint which is provided with a lubricating coating layer formed from the composition and has excellent seizure resistance and excellent high torque performance. [Means for solving the problem]

[0017] The composition according to the present disclosure is a composition for forming a lubricating coating layer on a tubular threaded joint, and contains polyisobutylene, a metal soap, a wax, and a basic metal salt of an aromatic organic acid.

[0018] A tubular threaded joint according to the present disclosure comprises a pin having a pin side contact surface including a pin side thread portion, a box having a box side contact surface including a box side thread portion, and a lubricating coating layer made of the above composition as an outermost layer on at least one of the pin side contact surface and the box side contact surface. Effect of the Invention

[0019] A tubular threaded joint according to the present disclosure has as its outermost layer a lubricating coating layer containing polyisobutylene, a metal soap, a wax, and a metal salt of a basic aromatic organic acid. Therefore, the tubular threaded joint according to the present disclosure has excellent seizure resistance even when repeatedly made up. The tubular threaded joint according to the present disclosure further has excellent high torque performance. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a diagram showing the relationship between the torque and the rotation speed of a steel pipe when a tubular threaded joint having a shoulder is screwed up. [Diagram 2] FIG. 2 shows the results of a Falex test carried out using the compositions of test numbers 9 and 11 in the examples. [Diagram 3] FIG. 3 is a graph showing the relationship between the polyisobutylene content (mass %) in the lubricating coating layer and torque-on-shoulder resistance ΔT′ (relative value). [Figure 4] FIG. 4 is a graph showing the relationship between the polyisobutylene content (mass %) in a lubricating coating layer and seizure resistance. [Diagram 5] FIG. 5 is a diagram showing the configuration of a coupling-type threaded joint for pipes according to the present embodiment. [Figure 6] FIG. 6 is a diagram showing the configuration of an integral type tubular threaded joint according to the present embodiment. [Figure 7] FIG. 7 is a cross-sectional view of a tubular threaded joint. [Figure 8] FIG. 8 is a diagram showing the configuration of a threaded joint for pipes according to the present embodiment that does not have a metal seal portion or a shoulder portion. [Figure 9]FIG. 9 is a cross-sectional view of a tubular threaded joint according to the present embodiment. [Figure 10] FIG. 10 is a cross-sectional view of a pipe threaded joint according to another embodiment different from that of FIG. [Figure 11] FIG. 11 is a cross-sectional view of a pipe threaded joint according to another embodiment different from FIGS. [Figure 12] FIG. 12 is a diagram for explaining the torque-on shoulder resistance ΔT′ in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the present embodiment will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are designated by the same reference characters and their description will not be repeated.

[0022] The present inventors have conducted extensive investigations into the relationship between a composition for forming a lubricating coating layer on a tubular threaded joint and the seizure resistance and high torque performance of the tubular threaded joint, resulting in the following findings.

[0023] When steel pipes are screwed together, the optimum torque for completing screw tightening is determined in advance. Figure 1 is a diagram showing the relationship between the rotation speed of a steel pipe and the torque when a pipe threaded joint having a shoulder portion is screwed. Figure 1 is also called a torque chart. Referring to Figure 1, when a pipe threaded joint is screwed, the torque initially increases in proportion to the rotation speed. The rate of increase in torque at this time is low. If the screw is further screwed, the shoulder portions come into contact with each other. The torque at this time is called shouldering torque. If the screw is further screwed after the shouldering torque is reached, the torque again increases in proportion to the rotation speed. The rate of increase in torque at this time is higher than before the shouldering torque is reached. Screw tightening is completed when the torque reaches a specified value (fastening torque).

[0024] If the torque when tightening the threads reaches the tightening torque, the metal seal parts will interfere with each other with the appropriate surface pressure. In this case, the airtightness of the tubular threaded joint is improved. Furthermore, in oil wells, the threaded joint is subjected to high compressive stress and high bending stress. In order for the tubular threaded joint to not loosen even under such stress, it is necessary for the tubular threaded joint to be tightened with a sufficiently high torque (appropriate tightening torque).

[0025] If further tightening is performed after the tightening torque is reached, the torque will become too high. If the torque becomes too high, parts of the pin and box will undergo plastic deformation. The torque at this time is called yield torque. If the torque-on-shoulder resistance ΔT', which is the difference between the shouldering torque and the yield torque, is large, there will be more room in the range of the tightening torque. As a result, it becomes easier to adjust the tightening torque. Therefore, it is preferable for the torque-on-shoulder resistance ΔT' to be large.

[0026] In order to increase the torque-on-shoulder resistance ΔT', it is effective to reduce the shouldering torque or increase the yield torque. However, even if the composition of the lubricating coating layer is simply changed so that the friction coefficient increases or decreases, the shouldering torque and the yield torque generally behave in the same way. For example, when the friction coefficient of the lubricating coating layer increases, the yield torque increases, but the shouldering torque also increases (called high shouldering). As a result, even if a certain tightening torque is reached, the shoulder surface may not come into contact and tightening may not be completed (called no shouldering). Conversely, when the friction coefficient of the lubricating coating layer decreases, the shouldering torque decreases, but the yield torque also decreases. As a result, the shoulder portion or seal portion may yield at a low tightening torque, and tightening may not be possible at a high tightening torque.

[0027] As a result of intensive research by the present inventors, they have discovered something previously unknown: that by incorporating polyisobutylene into the lubricating coating layer, it is possible to increase the yield torque and increase the torque-on-shoulder resistance ΔT' while maintaining the shouldering torque at the same level as before. This point will be explained in detail with reference to the drawings.

[0028] FIG. 2 is a diagram showing the results of a Falex test using the compositions shown in Test No. 9 and Test No. 11 in the examples. The Falex test is a test in which a rotating journal pin is sandwiched between two V-shaped blocks, and the load applied to the blocks and the friction torque generated by applying the load are measured. A method for measuring the seizure load by the Falex test is specified, for example, in ASTM D 3233. FIG. 2 is a line graph showing the results of measuring the load applied to the blocks and the friction torque generated between the rotating journal pin and the V-shaped blocks by applying the composition of Test No. 9 or Test No. 11 to the surface of the journal pin and rotating the journal pin. The vertical axis of FIG. 2 indicates the friction torque. The horizontal axis of FIG. 2 indicates the load applied to the blocks.

[0029] Referring to FIG. 2, the torque increases from a low load to a certain range in both the case of using the composition of test number 9 and the case of using the composition of test number 11. However, when the composition of test number 11 not containing polyisobutylene was used, the torque increase rate decreased when the load increased to a certain level. This means that when the load (surface pressure) applied to the metal seal portion and the shoulder portion increases sharply in the final stage of the screw tightening in FIG. 1, the torque increase rate becomes slow in the composition not containing polyisobutylene. In other words, in the region where the rotation speed is higher than the shouldering torque in the torque chart shown in FIG. 1, the torque increase rate immediately after shouldering cannot be maintained. In this case, the yield torque cannot be increased. However, when the composition of test number 9 containing polyisobutylene was used, the torque increase rate did not decrease even after the load increased to a certain level. This means that the torque continues to increase even when the load (surface pressure) increases sharply in the final stage of the screw tightening in FIG. 1. In other words, the torque increase rate immediately after shouldering is maintained in the region where the rotation speed is higher than the shouldering torque in the torque chart shown in Figure 1. In this case, the yield torque can be increased.

[0030] By increasing the yield torque while suppressing the shouldering torque, the torque-on-shoulder resistance ΔT' increases. FIG. 3 is a diagram showing the relationship between the content (mass%) of polyisobutylene in the lubricating coating layer and the torque-on-shoulder resistance ΔT' (relative value). FIG. 3 was obtained from an example described later. The vertical axis of FIG. 3 indicates the torque-on-shoulder resistance ΔT' (relative value). The horizontal axis of FIG. 3 indicates the content (mass%) of polyisobutylene in the lubricating coating layer. Each value of the torque-on-shoulder resistance ΔT' (relative value) is a value obtained as a relative value with the value of the torque-on-shoulder resistance ΔT' when an API standard dope is used instead of the lubricating coating layer set as a reference (100). The white circle (○) in FIG. 3 indicates the torque-on-shoulder resistance ΔT' (relative value) of the example in which the lubricating coating layer is formed. The triangle (△) in FIG. 3 indicates the torque-on-shoulder resistance ΔT' (reference value, i.e., 100) when an API standard dope is used instead of the lubricating coating layer.

[0031] Referring to FIG. 3, in test number 11, which did not contain polyisobutylene, the torque-on-shoulder resistance ΔT' (relative value) was 60. On the other hand, in test number 9, which contained polyisobutylene, the torque-on-shoulder resistance ΔT' (relative value) was 115. In the tubular threaded joint provided with a lubricating coating layer made of a composition containing polyisobutylene, the torque increased steadily even under high surface pressure in the final stage of screw tightening without increasing the shouldering torque. Therefore, the yield torque increased. As a result, the torque-on-shoulder resistance ΔT' (relative value) exceeded 100.

[0032] 3, it can be seen that when the lubricating coating layer contains polyisobutylene, the torque-on-shoulder resistance ΔT' (relative value) exceeds 100 in the other examples as well. In other words, when the lubricating coating layer contains polyisobutylene, excellent high torque performance can be obtained.

[0033] The present inventors further discovered that when the lubricating coating layer contains polyisobutylene, it provides seizure resistance that is equal to or greater than that of conventional API dopes.

[0034] Figure 4 shows the relationship between the polyisobutylene content (mass%) in the lubricating coating layer and seizure resistance. Figure 4 was obtained from an example described later. The vertical axis of Figure 4 shows the number of times make-up was possible without irrecoverable seizure occurring in the threaded portion or without seizure occurring in the metal seal portion. The horizontal axis of Figure 4 shows the polyisobutylene content (mass%) in the lubricating coating layer.

[0035] Referring to Figure 4, if the lubricating coating layer contains polyisobutylene, the number of times that the screw can be repeatedly tightened without seizure occurring is 10 or more, which is the same as with the conventional API dope. In other words, if the lubricating coating layer contains polyisobutylene, not only is excellent high torque performance obtained, but also excellent seizure resistance is obtained.

[0036] As described above, when a lubricating coating layer contains polyisobutylene, not only excellent high torque performance but also excellent seizure resistance can be obtained. The detailed mechanism by which the inclusion of polyisobutylene in a lubricating coating layer improves the high torque performance and seizure resistance of a tubular threaded joint has not been clarified. However, the present inventors believe as follows.

[0037] Polyisobutylene is a semi-solid polymer at room temperature (approximately 25°C) and is thought to dissolve easily in the wax contained in the lubricating coating layer. Polyisobutylene may also be able to suppress a decrease in the viscosity of the wax even when the temperature rises when the tubular threaded joint slides. As a result, it is thought that high torque performance of the tubular threaded joint can be obtained. In this case, the viscosity of the wax in the lubricating coating layer is further maintained, so the thickness of the lubricating coating layer may be maintained. As a result, it is thought that seizure resistance may be improved.

[0038] The composition of the present embodiment, which was completed based on the above findings, is a composition for forming a lubricating coating layer on a tubular threaded joint, and contains polyisobutylene, a metal soap, a wax, and a metal salt of a basic aromatic organic acid.

[0039] The composition of the present embodiment contains polyisobutylene, a metal soap, a wax, and a basic metal salt of an aromatic organic acid, and therefore a tubular threaded joint provided with a lubricating coating layer made of this composition has excellent seizure resistance and excellent high torque performance.

[0040] Preferably, the composition contains, when the total amount of nonvolatile components in the composition is taken as 100 mass%, 5 to 30 mass% of polyisobutylene, 2 to 30 mass% of metal soap, 2 to 30 mass% of wax, and 10 to 70 mass% of basic aromatic organic acid metal salt.

[0041] In this case, the seizure resistance and high torque performance of the tubular threaded joint are further improved.

[0042] Preferably, the composition further contains a lubricating powder.

[0043] In this case, the lubricity of the tubular threaded joint is improved.

[0044] Preferably, the composition contains 0.5 to 20 mass % of a lubricating powder when the total amount of non-volatile components in the composition is taken as 100 mass %.

[0045] Preferably, the lubricating powder is one or two selected from the group consisting of graphite and polytetrafluoroethylene.

[0046] The composition may further contain a volatile organic solvent.

[0047] A tubular threaded joint of this embodiment comprises a pin having a pin side contact surface including a pin side thread portion, a box having a box side contact surface including a box side thread portion, and a lubricating coating layer made of the above composition as an outermost layer on at least one of the pin side contact surface and the box side contact surface.

[0048] If a tubular threaded joint is provided with a lubricating coating layer, as an outermost layer, on at least one of the pin side contact surface and the box side contact surface, which is made of a composition containing polyisobutylene, a metal soap, a wax, and a basic aromatic organic acid metal salt, the seizure resistance and high torque performance of the tubular threaded joint are improved.

[0049] A tubular threaded joint may be provided with the above-described lubricating coating layer on the pin-side contact surface.

[0050] Preferably, the tubular threaded joint further comprises a plating layer between the pin-side contact surface and the lubricating coating layer.

[0051] In this case, the seizure resistance and corrosion resistance of the tubular threaded joint are improved.

[0052] Preferably, the threaded joint for pipes further comprises a chemical conversion coating between the lubricating coating layer and the plating layer.

[0053] In this case, the adhesion of the lubricating coating layer is improved.

[0054] Preferably, when the tubular threaded joint does not have a plating layer, the pin side contact surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling, and when the tubular threaded joint is provided with a plating layer, the plating layer surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling.

[0055] The threaded joint for pipes may be provided with the above-mentioned lubricating coating layer on the box side contact surface.

[0056] Preferably, the threaded joint for pipes further comprises a plating layer between the box side contact surface and the lubricating coating layer.

[0057] In this case, the seizure resistance and corrosion resistance of the tubular threaded joint are improved.

[0058] Preferably, the threaded joint for pipes further comprises a chemical conversion coating between the lubricating coating layer and the plating layer.

[0059] In this case, the adhesion of the lubricating coating layer is improved.

[0060] Preferably, when the tubular threaded joint does not have a plating layer, the box side contact surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling, and when the tubular threaded joint has a plating layer, the plating layer surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling.

[0061] Preferably, the pin side contact surface of the tubular threaded joint further includes a pin side metal seal portion and a pin side shoulder portion, and the box side contact surface further includes a box side metal seal portion and a box side shoulder portion.

[0062] The composition according to this embodiment and a threaded joint for pipes provided with a lubricating coating layer formed from the composition will be described in detail below.

[0063] [Pipe threaded joints] The tubular threaded joint comprises a pin and a box. FIG. 5 is a diagram showing the configuration of a coupling-type tubular threaded joint according to this embodiment. Referring to FIG. 5, the tubular threaded joint comprises a steel pipe 1 and a coupling 2. A pin 3 having a pin-side threaded portion on the outer surface is formed at both ends of the steel pipe 1. A box 4 having a box-side threaded portion on the inner surface is formed at both ends of the coupling 2. The coupling 2 is attached to the end of the steel pipe 1 by screwing the pin 3 and the box 4 together. Although not shown, protectors may be attached to the pin 3 of the steel pipe 1 and the box 4 of the coupling 2 to which no mating member is attached, in order to protect the respective threaded portions.

[0064] On the other hand, an integral type tubular threaded joint may be used in which one end of a steel pipe 1 is a pin 3 and the other end is a box 4 without using a coupling 2. FIG. 6 is a diagram showing the configuration of an integral type tubular threaded joint according to this embodiment. Referring to FIG. 6, the tubular threaded joint includes a steel pipe 1. At one end of the steel pipe 1, a pin 3 having a pin side thread portion on its outer surface is formed. At the other end of the steel pipe 1, a box 4 having a box side thread portion on its inner surface is formed. The steel pipes 1 can be connected to each other by screwing the pin 3 and the box 4 together. The tubular threaded joint of this embodiment can be used for both coupling type and integral type tubular threaded joints.

[0065] FIG. 7 is a cross-sectional view of a pipe threaded joint. In FIG. 7, the pin 3 includes a pin side threaded portion 31, a pin side metal seal portion 32, and a pin side shoulder portion 33. In FIG. 7, the box 4 includes a box side threaded portion 41, a box side metal seal portion 42, and a box side shoulder portion 43. The portions that come into contact when the pin 3 and the box 4 are screwed together are called contact surfaces 34 and 44. Specifically, when the pin 3 and the box 4 are screwed together, the threaded portions (the pin side threaded portion 31 and the box side threaded portion 41), the metal seal portions (the pin side metal seal portion 32 and the box side metal seal portion 42), and the shoulder portions (the pin side shoulder portion 33 and the box side shoulder portion 43) come into contact with each other. In FIG. 7, the pin side contact surface 34 includes the pin side threaded portion 31, the pin side metal seal portion 32, and the pin side shoulder portion 33. In FIG. 7, the box side contact surface 44 includes a box side thread portion 41 , a box side metal seal portion 42 and a box side shoulder portion 43 .

[0066] In FIG. 7, in the pin 3, the pin side shoulder portion 33, the pin side metal seal portion 32, and the pin side thread portion 31 are arranged in this order from the end of the steel pipe 1. In the box 4, the box side thread portion 41, the box side metal seal portion 42, and the box side shoulder portion 43 are arranged in this order from the end of the steel pipe 1 or the coupling 2. However, the arrangement of the pin side thread portion 31 and the box side thread portion 41, the pin side metal seal portion 32 and the box side metal seal portion 42, and the pin side shoulder portion 33 and the box side shoulder portion 43 is not limited to the arrangement in FIG. 7, and can be changed as appropriate. For example, as shown in FIG. 6, in the pin 3, the pin side metal seal portion 32, the pin side thread portion 31, the pin side metal seal portion 32, the pin side shoulder portion 33, the pin side metal seal portion 32, and the pin side thread portion 31 may be arranged in this order from the end of the steel pipe 1. In the box 4, from the end of the steel pipe 1 or the coupling 2, the box side metal seal portion 42, the box side threaded portion 41, the box side metal seal portion 42, the box side shoulder portion 43, the box side metal seal portion 42 and the box side threaded portion 41 may be arranged in this order.

[0067] 5 and 6 show a so-called premium joint having a metal seal portion (pin side metal seal portion 32 and box side metal seal portion 42) and a shoulder portion (pin side shoulder portion 33 and box side shoulder portion 43). However, the metal seal portion (pin side metal seal portion 32 and box side metal seal portion 42) and the shoulder portion (pin side shoulder portion 33 and box side shoulder portion 43) may be omitted. FIG. 8 shows an example of a tubular threaded joint having no metal seal portion 32, 42 and no shoulder portion 33, 43. The lubricating coating layer of this embodiment can be suitably applied to a tubular threaded joint having no metal seal portion 32, 42 and no shoulder portion 33, 43. In the absence of the metal seal portion 32, 42 and no shoulder portion 33, 43, the pin side contact surface 34 includes the pin side thread portion 31. In the absence of the metal seal portion 32, 42 and no shoulder portion 33, 43, the box side contact surface 44 includes the box side thread portion 41.

[0068] [Lubricating film layer] The tubular threaded joint is provided with a lubricating coating layer on at least one of the pin side contact surface 34 and the box side contact surface 44. Figure 9 is a cross-sectional view of a tubular threaded joint according to this embodiment. The lubricating coating layer 21 is formed by applying a composition for forming the lubricating coating layer 21 to at least one of the pin side contact surface 34 and the box side contact surface 44, and then drying it, as in the manufacturing method described below.

[0069] [Composition for forming lubricating coating layer 21] The composition for forming the lubricating coating layer 21 contains polyisobutylene, a metal soap, a wax, and a metal salt of a basic aromatic organic acid. Thus, the lubricating coating layer 21 also contains polyisobutylene, a metal soap, a wax, and a metal salt of a basic aromatic organic acid. The composition may be a solvent-free composition (i.e., containing only the above-mentioned components) or a solvent-based composition dissolved in a solvent. In the case of a solvent-based composition, the mass % of each component refers to the mass % when the total amount of non-volatile components of the composition (the total mass of all components other than the solvent contained in the composition) is taken as 100%. In other words, the content of each component in the composition is the same as the content of each component in the lubricating coating layer 21. Hereinafter, the composition for forming the lubricating coating layer 21 will also be simply referred to as the "composition".

[0070] Each component in the composition will be described in detail below. Unless otherwise specified, "%" for each component means mass% based on the total amount of non-volatile components in the composition. In this embodiment, non-volatile components mean all components other than the solvent contained in the composition. Examples of non-volatile components include polyisobutylene, metal soap, wax, and basic aromatic organic acid metal salt.

[0071] [Polyisobutylene] Polyisobutylene has the general formula -(-C(CH3)2-CH2-) n - is a polymer of isobutene represented by the formula: Polyisobutylene is chemically inactive because it does not have an unsaturated bond in the molecule, and has strong resistance to ozone, acid, alkali, etc. Polyisobutylene is a semi-solid polymer with high viscosity. Polyisobutylene has high adhesion and viscosity. When the composition contains polyisobutylene, it is estimated that the viscosity of the composition can be suppressed from decreasing even when sliding occurs at high temperatures. As a result, when the composition contains polyisobutylene, it is estimated that the friction resistance at the friction interface of the lubricating coating layer 21 increases rapidly under high surface pressure in the final stage of screw tightening, and high torque performance is improved.

[0072] As described above, if the composition contains polyisobutylene, the high torque performance of the tubular threaded joint is improved. Furthermore, if the composition contains polyisobutylene, the seizure resistance of the tubular threaded joint is improved to the same level as or higher than that of the conventional API dope.

[0073] The polyisobutylene content is preferably 5 to 30%. If the polyisobutylene content is 5% or more, sufficient high torque performance can be stably obtained. Therefore, the lower limit of the polyisobutylene content is preferably 5%, more preferably 8%, and even more preferably 10%. On the other hand, if the polyisobutylene content is 30% or less, a decrease in the strength of the lubricating coating layer 21 can be suppressed. If the polyisobutylene content is 25% or less, an increase in friction can be further suppressed and high seizure resistance can be maintained. Therefore, the upper limit of the polyisobutylene content in the lubricating coating layer 21 is preferably 30%, and more preferably 25%.

[0074] The average molecular weight (Mv) of polyisobutylene is preferably 30,000 or more. Therefore, the lower limit of the average molecular weight of polyisobutylene is preferably 30,000, more preferably 50,000. On the other hand, if the average molecular weight of polyisobutylene is 100,000 or less, the viscosity of the composition is kept within an appropriate range, and the productivity is improved. Therefore, the upper limit of the average molecular weight of polyisobutylene is preferably 100,000, more preferably 90,000, and even more preferably 70,000.

[0075] In this specification, the average molecular weight (Mv) of polyisobutylene refers to the viscosity average molecular weight. The viscosity average molecular weight is measured by the following method. A capillary viscometer is used to measure the flow time of a diluting solution of polyisobutylene to determine the intrinsic viscosity [η]. The intrinsic viscosity [η] thus obtained is calculated using the Mark-Houwink equation ([η] = KM a ) to calculate the viscosity average molecular weight (Mv).

[0076] As the polyisobutylene, for example, Tetrax (registered trademark) (grades 3T to 6T) and Himol (product name) (grades 4H to 6H) manufactured by JXTG Nippon Oil & Energy Corporation can be used.

[0077] [Metal soap] Metal soap is a general term for all metal salts of fatty acids other than sodium and potassium. If the composition contains a metal soap, the galling resistance and rust prevention properties of the threaded joint for pipes are improved.

[0078] The fatty acid is a general term for saturated or unsaturated chain monocarboxylic acids. The fatty acid is, for example, one or more selected from the group consisting of lauric acid, tridecylic acid, myristic acid, palmitic acid, lanopalmitic acid, stearic acid, isostearic acid, 12-hydroxystearic acid, oleic acid, elaidic acid, arachic acid, behenic acid, erucic acid, lignoceric acid, lanoceric acid, ricinoleic acid, montanic acid, linoleic acid, linolenic acid, ricinolenic acid, octylic acid, and sebacic acid. The fatty acid of the metal soap is preferably one having 12 to 30 carbon atoms from the viewpoint of lubricity and rust prevention. The fatty acid having 12 to 30 carbon atoms is, for example, one or more selected from the group consisting of lauric acid, tridecylic acid, myristic acid, palmitic acid, lanopalmitic acid, stearic acid, isostearic acid, 12-hydroxystearic acid, oleic acid, elaidic acid, arachic acid, behenic acid, erucic acid, lignoceric acid, lanoceric acid, ricinoleic acid, montanic acid, linoleic acid, linolenic acid, and ricinolenic acid.

[0079] The metal of the metal soap is, for example, one or more selected from the group consisting of calcium, alkaline earth metals, zinc, aluminum and lithium. The metal is preferably calcium. The salt may be either a neutral salt or a basic salt.

[0080] The content of the metal soap in the composition is preferably 2-30%. A metal soap content of 2% or more sufficiently enhances the seizure resistance and rust prevention of the lubricating coating layer 21. A content of 30% or less further stably enhances the adhesion and strength of the lubricating coating layer 21. The lower limit of the metal soap content is more preferably 4%, and even more preferably 10%. The upper limit of the metal soap content is more preferably 19%, and even more preferably 17%.

[0081] [wax] Wax is a general term for organic substances that are solid at room temperature and become liquid when heated. The wax is one or more types selected from the group consisting of animal, vegetable, mineral and synthetic waxes. The animal wax is, for example, one or two types selected from the group consisting of beeswax and spermaceti. The vegetable wax is, for example, one or two types selected from the group consisting of Japan wax, carnauba wax, candelilla wax and rice wax. The mineral wax is, for example, one or two types selected from the group consisting of paraffin wax, microcrystalline wax, petrolatum, montan wax, ozokerite and ceresin. The synthetic wax is, for example, one or two types selected from the group consisting of oxidized wax, polyethylene wax, Fischer-Tropsch wax, amide wax and hardened castor oil (castor wax). As an example, the molecular weight of the wax is 1000 or less. Preferably, the wax is paraffin wax having a molecular weight of 150 to 500.

[0082] Wax reduces friction and improves the seizure resistance of the lubricant coating layer 21. Wax also reduces the fluidity of the lubricant coating layer 21 and improves the strength of the lubricant coating layer 21.

[0083] The wax content in the composition is preferably 2-30%. If the wax content is 2% or more, the above effects can be sufficiently obtained. If the wax content is 30% or less, the adhesion and strength of the lubricating coating layer 21 are more stably improved. The lower limit of the wax content is more preferably 5%, and even more preferably 10%. The upper limit of the wax content is more preferably 20%, and even more preferably 15%.

[0084] [Basic aromatic organic acid metal salts] The basic metal salt of an aromatic organic acid is a salt composed of an aromatic organic acid and an excess of an alkali (alkali metal or alkaline earth metal). The basic metal salt of an aromatic organic acid is, for example, a grease-like or semi-solid substance at room temperature.

[0085] The inclusion of a basic metal salt of an aromatic organic acid in the composition significantly enhances the corrosion resistance of the lubricating coating layer 21. The inclusion of a basic metal salt of an aromatic organic acid in the composition further enhances the seizure resistance of a tubular threaded joint. This effect is due to the fact that the basic metal salt of an aromatic organic acid is present in the lubricating coating layer 21 in the form of colloidal fine particles, causing the excess metal salt to be physically adsorbed or chemically adsorbed by the organic acid groups.

[0086] The aromatic organic acid is, for example, one or more selected from the group consisting of sulfonates, phenates, salicylates, and carboxylates.

[0087] The alkali constituting the cation portion of the basic aromatic organic acid metal salt is one or two selected from the group consisting of alkali metals and alkaline earth metals. Preferably, the alkali is one or two selected from the group consisting of alkaline earth metals. More preferably, the alkali is one or two selected from the group consisting of calcium, barium, and magnesium.

[0088] The higher the base number of the basic aromatic organic metal salt, the higher the amount of fine metal salt that functions as a solid lubricant. As a result, the seizure resistance of the lubricating coating layer 21 is improved. Furthermore, when the base number is higher than a certain level, it has the effect of neutralizing acid components. As a result, the rust prevention of the lubricating coating layer 21 is also improved. Therefore, the base number (JIS K2501 (2003)) of the basic aromatic organic metal salt (when two or more types are used, it means the weighted average of the base numbers taking into account the amount) is preferably 50 to 500 mgKOH / g. If the base number is 50 mgKOH / g or more, the above effect can be sufficiently obtained. If the base number is 500 mgKOH / g or less, the hydrophilicity can be reduced and sufficient rust prevention can be obtained. The lower limit of the base number of the basic aromatic organic metal salt is more preferably 100 mgKOH / g, even more preferably 200 mgKOH / g, and most preferably 250 mgKOH / g. The upper limit of the base number of the basic metal salt of an aromatic organic acid is more preferably 450 mgKOH / g. The base number of the basic metal salt of an aromatic organic acid is measured by a method in accordance with JIS K2501 (2003).

[0089] The content of the basic aromatic organic metal salt is preferably 10 to 70%. As described above, the basic aromatic organic metal salt is a grease-like or semi-solid substance and can also function as a base for the lubricating coating layer 21. Therefore, it can be contained in a large amount, up to 70% in the composition. Therefore, the upper limit of the content of the basic aromatic organic metal salt is preferably 70%, more preferably 60%, and even more preferably 55%. The lower limit of the content of the basic aromatic organic metal salt is preferably 10%, more preferably 20%, and even more preferably 40%.

[0090] [Lubricating powder] Preferably, the composition contains a lubricating powder to further enhance the lubricating properties of the lubricating coating layer 21. Lubricating powder is a general term for solid powders that have lubricating properties. Any known lubricating powder can be used.

[0091] Lubricating powders are roughly divided into, for example, the following four types: The lubricating powder contains one or more types selected from the group consisting of the following (1) to (4). (1) Materials that exhibit lubricity due to their specific slippery crystal structure, such as a hexagonal layered crystal structure (e.g., graphite, amorphous graphite, zinc oxide, boron nitride, and talc); (2) Those that exhibit lubricity due to the presence of reactive elements in addition to their crystalline structure (e.g., molybdenum disulfide, tungsten disulfide, graphite fluoride, tin sulfide, bismuth sulfide, and organic molybdenum), (3) Lubricating agents that exhibit lubricity due to chemical reactivity (e.g., thiosulfate compounds); (4) Those that exhibit lubricity through plastic or viscoplastic behavior under frictional stress (e.g., polytetrafluoroethylene (PTFE), polyamide, copper (Cu), and melamine cyanurate (MCA)).

[0092] Preferably, the lubricating powder contains one or more selected from the group consisting of (1) to (4). That is, preferably, the lubricating powder is one or more selected from the group consisting of graphite, amorphous graphite, zinc oxide, boron nitride, talc, molybdenum disulfide, tungsten disulfide, graphite fluoride, tin sulfide, bismuth sulfide, organic molybdenum, thiosulfate compounds, polytetrafluoroethylene (PTFE), polyamide, copper (Cu), and melamine cyanurate (MCA). More preferably, the lubricating powder is one or more selected from the group consisting of molybdenum disulfide, graphite, polytetrafluoroethylene (PTFE), and graphite fluoride. More preferably, the lubricating powder is one or more selected from the group consisting of graphite and polytetrafluoroethylene (PTFE). The lubricating powder is preferably graphite from the viewpoints of adhesion and rust prevention of the lubricating coating layer 21, and amorphous graphite is preferable from the viewpoint of film-forming properties. The lubricating powder is preferably polytetrafluoroethylene (PTFE) from the viewpoint of lubricity.

[0093] The content of the lubricating powder in the composition is preferably 0.5 to 20%. If the content of the lubricating powder is 0.5% or more, the seizure resistance of the tubular threaded joint is further improved. This increases the number of times that the screw can be tightened and unscrewed without seizure occurring. On the other hand, if the content of the lubricating powder is 20% or less, the strength of the lubricating coating layer 21 is further increased. This reduces wear of the lubricating coating layer 21. Therefore, the upper limit of the content of the lubricating powder is preferably 20%, more preferably 15%, and even more preferably 10%. The lower limit of the content of the lubricating powder is preferably 0.5%, more preferably 3%, and even more preferably 5%.

[0094] [Volatile organic solvents] The composition may contain a volatile organic solvent. When coating is performed at room temperature, a volatile organic solvent is added to a mixture of the components of the lubricating coating layer 21 to prepare the composition. Unlike substances contained in the composition, the volatile organic solvent evaporates during the lubricating coating layer formation process. Therefore, the volatile organic solvent usually does not substantially remain in the lubricating coating layer 21. However, since the lubricating coating layer 21 of this embodiment may be a viscous liquid or semi-solid, for example, 1% or less of the volatile organic solvent may remain. "Volatile" means that the coating shows a tendency to evaporate at temperatures from room temperature to 150°C.

[0095] The type of the volatile organic solvent is not particularly limited. The volatile organic solvent is, for example, a petroleum-based solvent. The petroleum-based solvent is, for example, one or more selected from the group consisting of solvents equivalent to industrial gasoline specified in JIS K2201 (2006), mineral spirits, aromatic petroleum naphtha, xylene, and cellosolve.

[0096] The volatile organic solvent preferably has a flash point of 30° C. or higher, an initial boiling point of 150° C. or higher, and an end point of 210° C. or lower. In this case, the volatile organic solvent is relatively easy to handle, evaporates quickly, and requires a short drying time.

[0097] The content of the volatile organic solvent may be appropriately adjusted so that the composition can be adjusted to an appropriate viscosity depending on the application method of the composition. The content of the volatile organic solvent is, for example, 20 to 50 g, assuming that the total amount of the non-volatile components is 100 g.

[0098] [Other ingredients] The composition may further contain known anti-rust additives, preservatives, color pigments, and the like.

[0099] [Anti-rust additives] It is preferable that the lubricating coating layer 21 has rust prevention properties for a long period of time until it is actually used. For this reason, the composition may contain a rust prevention additive. The rust prevention additive is a general term for additives that have corrosion resistance. The rust prevention additive is, for example, one or more types selected from the group consisting of aluminum tripolyphosphate, aluminum phosphite, and calcium ion-exchanged silica. Preferably, the rust prevention additive contains one or two types selected from the group consisting of calcium ion-exchanged silica and aluminum phosphite. Other examples of the rust prevention additive include commercially available reactive water repellents.

[0100] [Preservatives] The lubricating coating layer 21 may further contain an antiseptic. An antiseptic is a general term for additives that have corrosion resistance.

[0101] The total content of other components in the composition (anti-rust additives, preservatives, color pigments, etc.) is preferably 2-10 mass%. If the total content of other components is 2% or more, the rust prevention properties of the lubricating coating layer 21 are further stably improved. If the total content of other components is 10 mass% or less, the lubricity of the lubricating coating layer 21 is stably improved.

[0102] A composition for forming the lubricating coating layer 21 can be produced by mixing the above-mentioned polyisobutylene, metal soap, wax, basic aromatic organic acid metal salt, and other ingredients. The tubular threaded joint of this embodiment having the lubricating coating layer 21 can be produced by applying the composition to at least one of the pin side contact surface 34 and the box side contact surface 44 of a tubular threaded joint and then drying it.

[0103] [Thickness of lubricant film layer] The lubricating coating layer 21 preferably has a thickness of 10 to 40 μm. If the lubricating coating layer 21 is 10 μm or more, high lubricity can be stably obtained. On the other hand, if the lubricating coating layer 21 is 40 μm or less, the adhesion of the lubricating coating layer 21 is stable. If the lubricating coating layer 21 is 40 μm or less in thickness, the thread tolerance (clearance) of the sliding surface is further increased, and the surface pressure during sliding is reduced. As a result, the make-up torque can be prevented from becoming excessively high. Therefore, the lubricating coating layer 21 preferably has a thickness of 10 to 40 μm.

[0104] The thickness of the lubricating coating layer 21 is measured by the following method. Any measurement location (area: 5 mm × 20 mm) on the pin side contact surface 34 or box side contact surface 44 of a tubular threaded joint is wiped with absorbent cotton soaked in ethanol. The weight of the lubricating coating layer 21 is calculated from the difference in weight between the absorbent cotton before and after wiping. The average thickness of the lubricating coating layer 21 is calculated from the weight of the wiped lubricating coating layer 21, the density of the lubricating coating layer 21, and the area of ​​the measurement location.

[0105] [Layout of lubricant coating layer] The lubricating coating layer 21 is disposed as an outermost layer on at least one of the pin-side contact surface 34 and the box-side contact surface 44. As shown in Fig. 9, the lubricating coating layer 21 may be disposed only on the pin-side contact surface 34. As shown in Fig. 10, the lubricating coating layer 21 may be disposed only on the box-side contact surface 44. As shown in Fig. 11, the lubricating coating layer 21 may be disposed on both the pin-side contact surface 34 and the box-side contact surface 44.

[0106] The lubricating coating layer 21 may be disposed entirely or partially on at least one of the pin side contact surface 34 and the box side contact surface 44. When a tubular threaded joint has a metal seal portion (the pin side metal seal portion 32 and the box side metal seal portion 42) and a shoulder portion (the pin side shoulder portion 33 and the box side shoulder portion 43), the metal seal portions 32, 42 and the shoulder portions 33, 43 are subjected to particularly high surface pressure in the final stage of fastening. Therefore, when the lubricating coating layer 21 is disposed partially on at least one of the pin side contact surface 34 and the box side contact surface 44 having a metal seal portion (the pin side metal seal portion 32 and the box side metal seal portion 42) and a shoulder portion (the pin side shoulder portion 33 and the box side shoulder portion 43), the lubricating coating layer 21 may be disposed in at least one of the pin side metal seal portion 32, the box side metal seal portion 42, the pin side shoulder portion 33, and the box side shoulder portion 43. On the other hand, if the lubricating coating layer 21 is disposed over the entirety of at least one of the pin side contact surface 34 and the box side contact surface 44, the production efficiency of tubular threaded joints is improved.

[0107] The lubricating coating layer 21 may be a single layer or multiple layers. Multiple layers refers to a state in which the lubricating coating layer 21 is laminated in two or more layers on the contact surface 34 or 44 side. Two or more lubricating coating layers 21 can be formed by repeatedly applying and drying the composition. The lubricating coating layer 21 may be disposed directly on at least one of the pin-side contact surface 34 or the box-side contact surface 44, so long as it is disposed as the outermost layer on at least one of the pin-side contact surface 34 or the box-side contact surface 44, or may be disposed on top of a plating layer and / or a chemical conversion coating, which will be described later.

[0108] [Plating layer] Preferably, the tubular threaded joint of this embodiment further comprises a plating layer between the pin-side contact surface 34 and the lubricating coating layer 21 and / or between the box-side contact surface 44 and the lubricating coating layer 21. The plating layer is, for example, a single-layer plating layer of Cu, Sn or Ni metal, or a single-layer plating of a Cu-Sn alloy, a single-layer plating of a Zn-Co alloy, a single-layer plating of a Zn-Ni alloy, or a single-layer plating of a Cu-Sn-Zn alloy, a two-layer plating layer of a Cu layer and a Sn layer, or a three-layer plating layer of a Ni layer, a Cu layer and a Sn layer.

[0109] The hardness of the plating layer is preferably at least 300 in micro Vickers. If the hardness of the plating layer is at least 300, the corrosion resistance of the tubular threaded joint is further stably improved.

[0110] The hardness of the plating layer is measured as follows. Five areas are arbitrarily selected from the plating layer of a tubular threaded joint. For each selected area, the Vickers hardness (HV) is measured in accordance with JIS Z2244 (2009). The test conditions are room temperature (25°C) and a test force of 2.94 N (300 gf). The average of the obtained values ​​(a total of five) is defined as the hardness of the plating layer.

[0111] In the case of a multi-layer plating layer such as the above-mentioned two-layer plating layer of Cu layer and Sn layer, or a three-layer plating layer of Ni layer, Cu layer and Sn layer, the thickness of the bottom plating layer is preferably less than 1 μm. The thickness of the plating layer (total thickness in the case of multi-layer plating) is preferably 5 to 15 μm.

[0112] The thickness of the plating layer is measured as follows. The probe of an eddy current phase-based film thickness gauge conforming to ISO (International Organization for Standardization) 21968 (2005) is brought into contact with the surface of the plating layer. The phase difference between the high-frequency magnetic field at the input side of the probe and the eddy current excited by it on the plating layer is measured. This phase difference is converted into the thickness of the plating layer.

[0113] [Chemical conversion coating] Preferably, the tubular threaded joint of this embodiment further comprises a chemical conversion coating between the lubricating coating layer 21 and the plating layer. When the tubular threaded joint comprises a plating layer only on the pin-side contact surface 34, the chemical conversion coating is disposed between the plating layer on the pin-side contact surface 34 and the lubricating coating layer 21. When the tubular threaded joint comprises a plating layer only on the box-side contact surface 44, the chemical conversion coating is disposed between the plating layer on the box-side contact surface 44 and the lubricating coating layer 21. When the tubular threaded joint comprises plating layers on both the pin-side contact surface 34 and the box-side contact surface 44, the chemical conversion coating is disposed at least one of between the plating layer on the pin-side contact surface 34 and the lubricating coating layer 21 and between the plating layer on the box-side contact surface 44 and the lubricating coating layer 21.

[0114] Examples of the chemical conversion coating include a phosphate chemical conversion coating, an oxalate chemical conversion coating, and a borate chemical conversion coating. The chemical conversion coating is porous. Therefore, if the lubricating coating layer 21 is formed on the chemical conversion coating, the adhesion of the lubricating coating layer 21 is further improved due to the so-called "anchor effect." The preferred thickness of the chemical conversion coating is 5 to 40 μm. If the thickness of the chemical conversion coating is 5 μm or more, sufficient corrosion resistance can be ensured. If the thickness of the chemical conversion coating is 40 μm or less, the adhesion of the lubricating coating layer 21 is stably improved.

[0115] The thickness of the chemical conversion coating is determined by the following method. A tubular threaded joint on which a chemical conversion coating has been formed is cut in the thickness direction of the chemical conversion coating (perpendicular to the axial direction of the tubular threaded joint). The cross section of the chemical conversion coating is observed using an optical microscope at a magnification of 500 times, and the thickness of the chemical conversion coating is measured. If the thickness of the chemical conversion coating measured by the above measurement method is 10 μm or less, it is re-cut and measured again. In this case, the tubular threaded joint is cut in a direction inclined by 60° from the direction perpendicular to the axial direction of the tubular threaded joint. The cross section of the obtained chemical conversion coating is observed using an optical microscope at a magnification of 500 times, and the thickness of the chemical conversion coating is measured. If the thickness of the chemical conversion coating is measured again, the re-measured thickness is regarded as the thickness of the chemical conversion coating.

[0116] [Blast treatment or pickling] In the tubular threaded joint of this embodiment, the surface below the lubricating coating layer 21 that comes into contact with the lubricating coating layer 21 may be a surface that has been blasted or pickled. The surface below the lubricating coating layer 21 that comes into contact with the lubricating coating layer 21 is the pin-side contact surface 34 when the tubular threaded joint does not have a plating layer on the pin-side contact surface 34 (i.e., the lubricating coating layer 21 is formed directly on the pin-side contact surface 34), and is the plating layer surface when the tubular threaded joint has a plating layer on the pin-side contact surface 34. The surface below the lubricating coating layer 21 that comes into contact with the lubricating coating layer 21 is the box-side contact surface 44 when the tubular threaded joint does not have a plating layer on the box-side contact surface 44 (i.e., the lubricating coating layer 21 is formed directly on the box-side contact surface 44), and is the plating layer surface when the tubular threaded joint has a plating layer on the box-side contact surface 44.

[0117] The surface roughness is increased when the surface is blasted or pickled. More specifically, when the pin-side contact surface 34, the box-side contact surface 44, and the plating layer surface are blasted or pickled, the surface roughness of the pin-side contact surface 34, the box-side contact surface 44, and the plating layer surface is high. In this case, the adhesion of the lubricating coating layer 21 formed thereon is further increased. The surface roughness is preferably 1.0 to 8.0 μm in arithmetic mean roughness Ra. The larger the arithmetic mean roughness Ra, the larger the contact area with the lubricating coating layer 21. Therefore, the adhesion with the lubricating coating layer 21 is increased due to the anchor effect. If the adhesion of the lubricating coating layer 21 is increased, the seizure resistance of the tubular threaded joint is further increased. If the arithmetic mean roughness Ra is 1.0 μm or more, the adhesion of the lubricating coating layer 21 is further increased. If the arithmetic mean roughness Ra is 8.0 μm or less, friction is suppressed, and damage and peeling of the lubricating coating layer 21 are suppressed.

[0118] The arithmetic mean roughness Ra in this specification is measured based on JIS B 0601 (2001). It is measured using a scanning probe microscope SPI3800N manufactured by SII Nano Technology Co., Ltd. The measurement conditions are a 2 μm × 2 μm area of ​​the sample, and the number of acquired data is 1024 × 1024. The reference length is 2.5 mm.

[0119] [Arrangement of lubricant coating layer, plating layer and chemical conversion coating] As long as the lubricating coating layer 21 is disposed on at least one of the pin-side contact surface 34 and the box-side contact surface 44, the arrangement of the plating layer and the chemical conversion coating is not particularly limited. A case where only the lubricating coating layer 21 is provided is referred to as pattern 1. A case where the lubricating coating layer 21 is provided and a plating layer is provided thereunder is referred to as pattern 2. A case where the lubricating coating layer 21 is provided and a chemical conversion coating is provided thereunder is referred to as pattern 3. A case where the lubricating coating layer 21 is provided and a chemical conversion coating and a plating layer are provided thereunder is referred to as pattern 4. A case where the lubricating coating layer 21 is not provided is referred to as pattern 5. If the above conditions are satisfied, the pin-side contact surface 34 and the box-side contact surface 44 may be any of patterns 1 to 5. Specifically, when the pin-side contact surface 34 is pattern 1 to pattern 4, the box-side contact surface 44 may be any of patterns 1 to 5. Furthermore, when the pin-side contact surface 34 is pattern 5, the box-side contact surface 44 is any of patterns 1 to 4. Conversely, when the box side contact surface 44 is pattern 1 to pattern 4, the pin side contact surface 34 may be any of patterns 1 to 5. Furthermore, when the box side contact surface 44 is pattern 5, the pin side contact surface 34 is any of patterns 1 to 4. In any pattern, the pin side contact surface 34, the box side contact surface 44 and the plating layer surface may be surfaces that have been subjected to appropriate blasting or pickling.

[0120] [Base material for pipe thread joints] The composition of the base material of the tubular threaded joint is not particularly limited. The base material is, for example, carbon steel, stainless steel, alloy steel, etc. Among alloy steels, high alloy steels such as duplex stainless steel and Ni alloys containing alloy elements such as Cr, Ni, and Mo have high corrosion resistance. Therefore, if these high alloy steels are used as the base material, excellent corrosion resistance can be obtained in corrosive environments containing hydrogen sulfide, carbon dioxide, etc.

[0121] [Manufacturing method] The method for manufacturing a tubular threaded joint according to this embodiment will now be described.

[0122] The method for manufacturing a tubular threaded joint according to this embodiment includes a lubricant coating layer formation step of forming a lubricant coating layer 21 on at least one of the pin side contact surface 34 and the box side contact surface 44 using the composition of this embodiment.

[0123] [Lubricating film layer formation process] In the lubricating coating layer formation step, a mixture of the components of the composition described above is liquefied by adding a solvent and / or by heating, and the liquid is applied to at least one of the pin side contact surface 34 and the box side contact surface 44. If necessary, the composition applied to at least one of the pin side contact surface 34 and the box side contact surface 44 is dried to form the lubricating coating layer 21. The nature of the lubricating coating layer 21 is not important. The nature of the lubricating coating layer 21 is, for example, a solid, a viscous liquid, or a semi-solid.

[0124] First, a composition is produced. For example, a solventless composition can be produced by heating a mixture of polyisobutylene, a metal soap, a wax, and a basic aromatic organic acid metal salt, and kneading the mixture in a molten state. A powder mixture in which all components are mixed in powder form may also be used as the composition.

[0125] The solvent-based composition can be produced, for example, by mixing polyisobutylene, a metal soap, a wax, and a basic aromatic organic acid metal salt in a volatile organic solvent.

[0126] In the case of a solvent-free composition, the composition can be applied using a hot melt method. In the hot melt method, the composition is heated and melted to a low-viscosity fluid state. The fluidized composition is sprayed from a spray gun having a temperature maintenance function. The composition is heated and melted in a tank equipped with a suitable stirring device, and is supplied to the spray head of the spray gun (maintained at a predetermined temperature) via a metering pump by a compressor, and sprayed. The heating temperature is, for example, 90 to 130°C. The holding temperature in the tank and the spray head is adjusted according to the melting points of the components of the composition. The application method may be brush application, immersion, etc., instead of spray application. The heating temperature of the composition is preferably 10 to 50°C higher than the melting point of the composition. When applying the composition, it is preferable to heat at least one of the pin side contact surface 34 and the box side contact surface 44 to which the composition is applied to a temperature higher than the melting point of the base. This allows good coverage to be obtained.

[0127] In the case of a solvent-based composition, the composition in a solution state is applied to the contact surface by spray coating, etc. In this case, it is preferable to adjust the viscosity of the composition so that it can be spray-coated under an environment of normal temperature and normal pressure.

[0128] In the case of a solventless composition, the molten composition applied to at least one of the pin side contact surface 34 and the box side contact surface 44 is cooled to dry and form the lubricating coating layer 21. The cooling method can be a well-known method, such as air cooling or cooling in the air.

[0129] In the case of a solvent-based composition, the lubricating coating layer 21 is formed by drying the composition applied to at least one of the pin-side contact surface 34 and the box-side contact surface 44. The drying method can be a well-known method, such as natural drying, low-temperature air drying, and vacuum drying.

[0130] Cooling may be performed by rapid cooling using a nitrogen gas and carbon dioxide gas cooling system, etc. When rapid cooling is performed, cooling is performed indirectly from the opposite side of the pin side contact surface 34 and / or box side contact surface 44 to which the composition is applied (the outer surface of the steel pipe 1 or coupling 2 in the case of the box 4, and the inner surface of the steel pipe 1 in the case of the pin 3). This makes it possible to suppress deterioration of the lubricating coating layer 21 due to rapid cooling.

[0131] The manufacturing method of this embodiment may include the following step prior to the lubricant coating layer forming step.

[0132] [Plating layer formation process] The method for manufacturing a tubular threaded joint according to this embodiment may include a plating layer forming step prior to the lubricating coating layer forming step. The plating layer can be formed by, for example, electroplating or impact plating.

[0133] [Electroplating process] The electroplating process is, for example, a process for forming a plating layer by electroplating. When forming a plating layer, in the electroplating process, a Zn alloy plating layer may be formed by electroplating on at least one of the pin-side contact surface 34 and the box-side contact surface 44. Alternatively, in the electroplating process, at least one of the pin-side contact surface 34 and the box-side contact surface 44 may be roughened by blasting or pickling, and then a Zn alloy plating layer may be formed by electroplating.

[0134] Electroplating treatment improves the seizure resistance and corrosion resistance of the pipe threaded joint. When forming a plating layer, the electroplating process may be, for example, a single-layer plating process using Cu, Sn or Ni metal, a single-layer plating process using a Cu-Sn alloy, a single-layer plating process using a Zn-Co alloy, a single-layer plating process using a Zn-Ni alloy, a single-layer plating process using a Cu-Sn-Zn alloy plating, a two-layer plating process using a Cu layer and a Sn layer, and a three-layer plating process using a Ni layer, a Cu layer and a Sn layer. For a steel pipe 1 made of steel with a Cr content of 5% or more, a Cu-Sn alloy plating process, a two-layer plating process using a Cu plating-Sn plating process, and a three-layer plating process using a Ni plating-Cu plating-Sn plating process are preferred.

[0135] The electroplating process can be performed by a known method. For example, a bath containing ions of the metal elements contained in the plating layer is prepared. Then, at least one of the pin side contact surface 34 and the box side contact surface 44 is immersed in the bath. A current is passed through the immersed pin side contact surface 34 and / or box side contact surface 44, thereby forming a plating layer on at least one of the pin side contact surface 34 and the box side contact surface 44. Conditions such as the bath temperature and plating time can be set appropriately.

[0136] More specifically, for example, when a Cu-Sn-Zn alloy plating layer is formed, the plating bath contains copper ions, tin ions, and zinc ions. The plating bath preferably has a composition of Cu: 1-50 g / L, Sn: 1-50 g / L, and Zn: 1-50 g / L. The electroplating conditions are, for example, plating bath pH: 1-10, plating bath temperature: 60° C., current density: 1-100 A / dm 2 And, the processing time is 0.1 to 30 minutes.

[0137] When forming a Zn-Ni alloy plating layer, the plating bath contains zinc ions and nickel ions. The plating bath preferably has a composition of Zn: 1 to 100 g / L and Ni: 1 to 50 g / L. The electroplating conditions are, for example, plating bath pH: 1 to 10, plating bath temperature: 60° C., current density: 1 to 100 A / dm 2 And, the processing time is 0.1 to 30 minutes.

[0138] [Impact plating process] Impact plating is a process that can be carried out by mechanical plating, in which particles and the object to be plated are collided in a rotating barrel, or projection plating, in which particles are collided with the object to be plated using a blasting device.

[0139] In the method for manufacturing a tubular threaded joint according to this embodiment, the surface in contact with the lubricating coating layer 21 may be subjected to blasting or pickling. Surface roughness can be formed by blasting or pickling. The surface in contact with the lubricating coating layer 21 is the pin-side contact surface 34 when the pin-side contact surface 34 does not have a plating layer, and is the plating layer when the pin-side contact surface 34 has a plating layer. The surface in contact with the lubricating coating layer 21 is the box-side contact surface 44 when the box-side contact surface 44 does not have a plating layer, and is the plating layer when the box-side contact surface 44 has a plating layer.

[0140] [Blast processing] The blasting process is, for example, a process in which particles are collided with the object to be plated using a blasting device. The blasting process is, for example, a sandblasting process. The sandblasting process is a process in which a blasting material (abrasive) is mixed with compressed air and projected onto the contact surfaces 34, 44. The blasting material is, for example, a spherical shot material and an angular grid material. The sandblasting process can increase the surface roughness of the pin-side contact surface 34, the box-side contact surface 44, or the plating layer. The sandblasting process can be performed by a well-known method. For example, air is compressed with a compressor, and the compressed air is mixed with the blasting material. The material of the blasting material is, for example, stainless steel, aluminum, ceramic, alumina, etc. The projection speed and other conditions of the sandblasting process can be set appropriately.

[0141] [Acid washing treatment] The pickling process is a process in which at least one of the pin-side contact surface 34 and the box-side contact surface 44 is immersed in a strong acid solution such as sulfuric acid, hydrochloric acid, nitric acid, or hydrofluoric acid to roughen the contact surface 34 or 44. This makes it possible to increase the surface roughness of the contact surface 34 or 44.

[0142] [Chemical conversion treatment] The method for manufacturing a tubular threaded joint according to this embodiment may include a chemical conversion treatment step prior to the lubricating coating layer forming step. Chemical conversion treatment is a treatment for forming a porous chemical conversion coating with large surface roughness. Examples of chemical conversion treatments include phosphate chemical conversion treatment, oxalate chemical conversion treatment, and borate chemical conversion treatment. From the viewpoint of adhesion of the lubricating coating layer 21, phosphate chemical conversion treatment is preferred. Examples of phosphate chemical conversion treatments include phosphate chemical conversion treatment using manganese phosphate, zinc phosphate, iron manganese phosphate, or zinc calcium phosphate.

[0143] The chemical conversion treatment can be carried out by a known method. As the treatment liquid, an acidic phosphate chemical conversion treatment liquid for general zinc-plated materials can be used. For example, a zinc phosphate-based chemical conversion treatment containing 1 to 150 g / L of phosphate ions, 3 to 70 g / L of zinc ions, 1 to 100 g / L of nitrate ions, and 0 to 30 g / L of nickel ions can be used. A manganese phosphate-based chemical conversion treatment liquid commonly used for pipe threaded joints can also be used. The liquid temperature is, for example, room temperature to 100°C. The treatment time can be appropriately set according to the desired film thickness, for example, 15 minutes. In order to promote the formation of the chemical conversion coating, surface conditioning may be performed before the chemical conversion treatment. The surface conditioning is a treatment of immersing in a surface conditioning aqueous solution containing colloidal titanium. After the chemical conversion treatment, it is preferable to wash with water or hot water and then dry.

[0144] The above-mentioned treatments before the formation of the lubricating coating layer may be carried out alone or in combination.

[0145] The treatment before the formation of the lubricating coating layer may be the same for pin 3 and box 4, or different for pin 3 and box 4. EXAMPLES

[0146] Examples of the present invention will be described below. However, the present invention is not limited to the examples. In the examples, the pin side contact surface is referred to as the pin surface, and the box side contact surface is referred to as the box surface. In addition, % in the examples means mass % unless otherwise specified.

[0147] In this example, the tubular threaded joint used was VAM21 (registered trademark) manufactured by Nippon Steel Corporation. VAM21 (registered trademark) is a tubular threaded joint with an outer diameter of 177.80 mm (7 inches) and a wall thickness of 11.506 mm (0.453 inches). The steel type was carbon steel. The carbon steel had a composition of C: 0.24%, Si: 0.23%, Mn: 0.7%, P: 0.02%, S: 0.01%, Cu: 0.04%, Ni: 0.05%, Cr: 0.95%, Mo: 0.15%, and the balance: Fe and impurities.

[0148] The pin surface and box surface of each test number were subjected to surface preparation as shown in Table 1. The numbers in the "Surface Preparation" column in Table 1 indicate the order in which the surface preparation was performed. For example, in the case of "1. Grinding Finish, 2. Zn Phosphate", the zinc phosphate conversion treatment was performed after grinding. In the sandblasting process, the abrasive grain Mesh100 was used to form the surface roughness. The arithmetic mean roughness Ra of each test number is as shown in Table 1. The arithmetic mean roughness Ra was measured based on JIS-B0601 (2013). The arithmetic mean roughness Ra was measured using a scanning probe microscope SPI3800N manufactured by SII Nanotechnology. The measurement conditions were a 2μm×2μm area of ​​the sample as the unit of the number of acquired data, and the number of acquired data was 1024×1024. The film thickness of the Zn-Ni alloy was measured using the measurement method described above.

[0149] [Table 1]

[0150] Thereafter, a lubricating coating layer was formed using a composition having the composition shown in Table 2 to prepare pins and boxes of each test number. In Table 2, the parentheses in the column "Non-volatile component composition of the composition" indicate the content in mass% based on the total amount of non-volatile components of the composition. As polyisobutylene, Tetrax (registered trademark) grade 3T (average molecular weight 30000), Tetrax (registered trademark) grade 4T (average molecular weight 40000), Tetrax (registered trademark) grade 5T (average molecular weight 50000), and Tetrax (registered trademark) grade 6T (average molecular weight 60000) manufactured by JXTG Energy Corporation were used. As metal soap, Ca-STEARATE (trade name) manufactured by Dainippon Ink and Chemicals, Inc. was used. As wax, Paraffin Wax (trade name) manufactured by Nippon Seiro Co., Ltd. was used. As basic aromatic organic acid metal salt, Calcinate (trade name) C400CLR (base number 400mgKOH / g) manufactured by CHEMTURA was used as basic Ca sulfonate. In the case of graphite, the lubricating powder used was graphite powder, Ao-P (trade name) (ash content 3.79%, crystallinity 96.9%, average particle size 7 μm) manufactured by Nippon Graphite Industries Co., Ltd. In the case of PTFE, the lubricating powder used was Lubron (registered trademark) L-5F manufactured by Daikin Industries, Ltd. The volatile organic solvent used was Exxsol (trade name) D40 manufactured by Exxon Mobil Corporation. In Table 2, it is shown as an organic solvent. In addition, in test number 12, a compound grease specified in API standard BUL 5A2 was used instead of the composition. An example using a compound grease was used as the standard for high torque performance described later.

[0151] [Table 2]

[0152] [Test No. 1] In test number 1, the pin surface and the box surface were mechanically ground to finish. After that, a composition for forming a lubricating coating layer was sprayed onto both the pin surface and the box surface at room temperature (about 25°C) to form a lubricating coating layer. The thickness of the lubricating coating layer was calculated using the weight of the composition applied per unit area and unit time and its specific gravity based on a given spray pressure and the distance to the target surface, and the lubricating coating layer was applied so that the target average thickness was in the range of 120 to 150 μm.

[0153] [Test No. 2 to Test No. 4 and Test No. 8 to Test No. 10] In test numbers 2 to 4 and test numbers 8 to 10, the pin surface and the box surface were subjected to mechanical grinding finishing. The pin was immersed in a zinc phosphate conversion treatment solution at 75 to 85°C for 10 minutes to form a zinc phosphate coating with a thickness of 10 μm. The box was immersed in a manganese phosphate conversion treatment solution at 80 to 95°C for 10 minutes to form a manganese phosphate coating with a thickness of 12 μm. Then, a composition for forming a lubricating coating layer was sprayed onto both the pin surface and the box surface at room temperature (about 20°C) to form a lubricating coating layer. The thickness of the lubricating coating layer was calculated by using the weight of the composition applied per unit area and unit time and its specific gravity from a predetermined spray pressure and a distance to the target surface, and the lubricating coating layer was applied so that the target average thickness was in the range of 120 to 150 μm.

[0154] [Test No. 5] In test number 5, the pin surface was subjected to mechanical grinding finishing. The pin was immersed in a zinc phosphate conversion treatment solution at 75 to 85°C for 10 minutes to form a zinc phosphate coating with a thickness of 10 μm. A composition for forming a lubricating coating layer was sprayed onto the pin at room temperature (about 25°C) to form a lubricating coating layer. The thickness of the lubricating coating layer was calculated using the weight of the composition applied per unit area and unit time and its specific gravity based on a given spray pressure and the distance to the target surface, and the lubricating coating layer was applied so that the target average thickness was in the range of 120 to 150 μm.

[0155] The box surface was mechanically ground to finish. Zn-Ni alloy plating was then performed on top of the surface by electroplating to form a Zn-Ni alloy plating layer. The Zn-Ni alloy plating bath used was Daijin Alloy N-PL, a product name of Daiwa Kasei Co., Ltd. The electroplating conditions were plating bath pH: 6.5, plating bath temperature: 25°C, current density: 2 A / dm 2 and treatment time: 18 minutes. The composition of the Zn-Ni alloy plating layer was Zn: 85% and Ni: 15%. A composition for forming a lubricating coating layer was heated (about 110°C) and sprayed thereon, and slowly cooled to form a lubricating coating layer. The thickness of the lubricating coating layer was calculated using the weight of the composition applied per unit area and unit time and its specific gravity from a given spray pressure and the distance to the target surface, and the coating was performed so that the target average thickness was in the range of 120 to 150 μm.

[0156] [Test No. 6 and Test No. 7] In test numbers 6 and 7, the pin surface and the box surface were mechanically ground to give a finish. Then, surface roughness was formed by blasting. Then, a composition for forming a lubricating coating layer was sprayed onto both the pin surface and the box surface at room temperature (about 20°C) to form a lubricating coating layer. The thickness of the lubricating coating layer was calculated using the weight of the composition applied per unit area and unit time and its specific gravity based on a given spray pressure and the distance to the target surface, and the lubricating coating layer was applied so that the target average thickness was in the range of 120 to 150 μm.

[0157] [Test No. 11] In test number 11, the pin surface and the box surface were subjected to mechanical grinding finishing. The pin surface was immersed in a zinc phosphate conversion treatment solution at 75 to 85°C for 10 minutes to form a zinc phosphate coating with a thickness of 10 μm. The box surface was immersed in a manganese phosphate conversion treatment solution at 80 to 95°C for 10 minutes to form a manganese phosphate coating with a thickness of 12 μm. Then, a composition for forming a lubricating coating layer was sprayed onto both the pin surface and the box surface at room temperature (about 25°C) to form a lubricating coating layer. The film thickness of the lubricating coating layer was calculated using the weight of the composition applied per unit area and unit time and its specific gravity from a predetermined spray pressure and a distance to the target surface, and the target average film thickness was set to be in the range of 120 to 150 μm. In test number 11, polyisobutylene was not contained in the composition.

[0158] [Test No. 12] In test number 12, the pin surface and the box surface were mechanically ground and finished, and then phosphate conversion coating was performed. API standard dope was then applied by brush. API standard dope is a compound grease for oil well pipe threads manufactured in accordance with API Bull 5A2. The composition of API standard dope is specified as a grease base material containing 18±1.0% graphite powder, 30.5±0.6% lead powder, and 3.3±0.3% copper flakes. It is understood that within this composition range, compound grease for oil well pipe threads has the same performance.

[0159] [Seizure resistance evaluation test] The seizure resistance was evaluated by a repeated fastening test. Using pins and boxes of test numbers 1 to 12, the screws were repeatedly tightened and loosened at room temperature (approximately 25°C) to evaluate the seizure resistance. The fastening torque was 24,350 N·m. The pin and box surfaces were visually observed after each screw tightening and loosening. The occurrence of seizure in the threads and metal seal was confirmed by visual observation. The test was terminated when seizure occurred in the metal seal. In cases where the seizure in the threads was minor and could be restored by care such as filing, the seizure damage was repaired and the test continued. The maximum number of repeated fastenings was 15. The evaluation index for seizure resistance was the maximum number of fastenings at which neither irreparable seizure occurred in the threads nor seizure occurred in the metal seal. The results are shown in the "Seizure resistance (number of times that it was possible to fasten without the occurrence of either irreparable seizure in the threads or seizure in the metal seal)" column in Table 3.

[0160] In addition, in test number 12, a new API dope was applied each time the screw was tightened and loosened. This is because API dope is usually applied anew each time the screw was tightened and loosened. In addition, API dope is only intended to be used in this manner. On the other hand, in test numbers 1 to 11, the test was continued until the end of the test without re-forming the lubricating coating layer.

[0161] [Table 3]

[0162] [High torque performance evaluation test] The torque-on-shoulder resistance ΔT' was measured using the pins and boxes of test numbers 1 to 12. Specifically, the screws were tightened at a tightening speed of 10 rpm and a tightening torque of 42.8 kN·m. The torque was measured during tightening, and a torque chart was created as shown in FIG. 12. Ts in FIG. 12 indicates the shouldering torque. MTV in FIG. 12 indicates the torque value at which the line segment L intersects with the torque chart. The line segment L has the same slope as the slope of the linear region in the torque chart after shouldering, and is a straight line with 0.2% more rotations than the linear region. Usually, when measuring the torque-on-shoulder resistance ΔT', Ty (yield torque) is used. However, in this embodiment, the yield torque (the boundary between the linear region and the nonlinear region in the torque chart after shouldering) was unclear. Therefore, the MTV was defined using the line segment L. The difference between MTV and Ts was taken as the torque-on-shoulder resistance ΔT' in this embodiment. The high torque performance was determined as a relative value of the torque-on-shoulder resistance ΔT' of this example to the torque-on-shoulder resistance ΔT' measured when an API standard dope was used instead of the lubricating coating layer in test number 12, which was set as the standard (100). The results are shown in Table 3.

[0163] [Evaluation Results] Referring to Tables 1 to 3, the compositions forming the lubricating coating layers of the tubular threaded joints of Test Nos. 1 to 10 contained polyisobutylene. Therefore, even when the threads were repeatedly tightened and loosened 10 times, no seizure occurred, demonstrating excellent seizure resistance. Furthermore, the high torque performance exceeded 100, demonstrating excellent high torque performance.

[0164] The tubular threaded joints of Test Nos. 1 to 5 and 8 to 10 had a polyisobutylene content of 5 to 30%. Therefore, the high torque performance was further improved compared to the tubular threaded joint of Test No. 6 (polyisobutylene content less than 5%). Furthermore, they could be made up more times without seizing than the tubular threaded joint of Test No. 7 (polyisobutylene content over 30%), demonstrating even better seizing resistance.

[0165] On the other hand, the composition forming the lubricating coating layer of the tubular threaded joint of test number 11 did not contain polyisobutylene. As a result, the number of times that it was possible to make up without seizure and the high torque performance were low.

[0166] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure. [Explanation of symbols]

[0167] 1 Steel pipe 2 Coupling 3-pin 4. Box 21 Lubricating film layer 31 Pin side thread 32 Pin side metal seal 33 Pin side shoulder 34 Pin side contact surface 41 Box side thread 42 Box side metal seal 43 Box side shoulder 44 Box side contact surface

Claims

1. A composition for forming a viscous liquid or semi-solid lubricating coating layer on a tubular threaded joint, comprising: When the total amount of nonvolatile components in the composition is 100 mass%, Polyisobutylene: 2 to 30% by mass, Metal soap: 2 to 30% by mass, Wax: 2 to 30% by mass, and A basic aromatic organic acid metal salt: 10 to 70 mass %; The composition, wherein the polyisobutylene has a viscosity average molecular weight of 30,000 to 100,000.

2. 2. The composition of claim 1 , When the total amount of nonvolatile components in the composition is 100 mass%, A composition comprising: 5 to 30 mass% polyisobutylene.

3. The composition of claim 1 or 2, further comprising: A composition comprising a lubricating powder.

4. 4. The composition of claim 3, When the total amount of nonvolatile components in the composition is 100 mass%, A composition comprising: 0.5 to 20 mass % of a lubricating powder.

5. 5. The composition according to claim 3 or 4, The composition, wherein the lubricating powder is one or two selected from the group consisting of graphite and polytetrafluoroethylene.

6. The composition according to any one of claims 1 to 5, further comprising: A composition comprising a volatile organic solvent.

7. A pipe threaded joint, comprising: a pin having a pin contact surface including a pin thread; a box having a box side contact surface including a box side thread portion; 7. A tubular threaded joint comprising, as an outermost layer, a viscous liquid or semi-solid lubricating coating layer comprising the composition according to any one of claims 1 to 6 on at least one of the pin side contact surface and the box side contact surface.

8. A tubular threaded joint according to claim 7, A threaded joint for pipes, comprising the lubricating coating layer on the pin side contact surface.

9. A tubular threaded joint according to claim 8, further comprising: A threaded joint for pipes, comprising: a plating layer between the pin side contact surface and the lubricating coating layer.

10. A tubular threaded joint according to claim 9, further comprising: A threaded joint for pipes, comprising a chemical conversion coating between the lubricating coating layer and the plating layer.

11. A tubular threaded joint according to claim 8 or claim 9, When the plated layer is not provided, the pin-side contact surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling, A threaded joint for pipes, wherein when the plating layer is provided, the surface of the plating layer is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling.

12. A tubular threaded joint according to claim 7, A threaded joint for pipes, comprising the lubricating coating layer on the box side contact surface.

13. A tubular threaded joint according to claim 12, further comprising: A threaded joint for pipes, comprising a plating layer between the box side contact surface and the lubricating coating layer.

14. A tubular threaded joint according to claim 13, further comprising: A threaded joint for pipes, comprising a chemical conversion coating between the lubricating coating layer and the plating layer.

15. A tubular threaded joint according to claim 12 or 13, When the plated layer is not provided, the box-side contact surface is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling, A threaded joint for pipes, wherein when the plating layer is provided, the surface of the plating layer is a surface that has been subjected to one or two treatments selected from the group consisting of blast treatment and pickling.

16. A tubular threaded joint according to any one of claims 7 to 15, the pin side contact surface further includes a pin side metal seal portion and a pin side shoulder portion; The box side contact surface further includes a box side metal seal portion and a box side shoulder portion.

Citation Information

Patent Citations

  • Abrasion-resistant threaded elements for threaded pipe joints

    JP2004507698A

  • Tubular threaded element with dry protective coating

    JP2009512819A

  • A lubricant composition exhibiting friction coefficient adaptability for threaded elements of tubular threaded connector components.

    JP2010523785A

  • Pipe thread fittings with excellent high-torque tightening characteristics.

    JP2014501885A

  • Pipe threaded fittings

    JP2014535023A